Effect of Liquid Culture Systems (Temporary Immersion Bioreactor and Rotary Shaker) Used During Multiplication and Differentiation on Efficiency of Repetitive Somatic Embryogenesis of Narcissus L. ‘Carlton’ - Małgorzata Malik; Ewelina Tomiak; Bożena Pawłowska (Agronomy)
Liquid culture systems, including bioreactors, are valuable tools for the scaling up of production. Their involvement leads to the automation of the highly efficient, reproducible somatic embryogenesis of Narcissus L. ‘Carlton’. Alternative procedures for efficient embryogenic tissue and early somatic embryo multiplication have been developed. The long-term embryogenic callus of narcissus ‘Carlton’, obtained by repetitive somatic embryogenesis, was multiplicated and differentiated in different liquid culture systems. For multiplication, the Rita® temporary immersion bioreactor and the rotary shaker at 60 rpm and 100 rpm were used, and, for differentiation, the rotary shaker at 60 rpm and solid cultures were investigated. Cultures immersed with a frequency of 15 min every 24 h during multiplication were characterized by the greatest increase in biomass (1.3), and the greatest number of embryos (152.6 embryos per 1 g of inoculum) was seen during differentiation. Higher immersion frequencies (15 min every 8 and 12 h) decreased the tissue quality and yield. The use of a bioreactor during multiplication promoted the number of embryos obtained during differentiation. In turn, cultivation in a rotary shaker during differentiation, regardless of the multiplication system, stimulated the multiplication of embryogenic tissue. The liquid medium used for the multiplication and differentiation of somatic embryos improved the synchronization of their development, which reached up to 95–99% depending on the system.